Prevalence of Tick-Borne Haemoprasites in Dogs in Agartala, Tripura - Bhowmik, Pratik; Islam, Saidul; Neog, Ranjeet; Borah, Rumi Saikia; De, Ankan; Monsang, Shongsir Warson; Kumar, Mritunjay (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dogs usually suffer from numerous parasitic diseases and among which tick-borne haemoparasitic infection is one of the major concerns.  Common tick-borne haemoparasites which cause disease in dogs are Babesia canis, B. gibsoni, Hepatozoon canis and rickettsial parasites  viz. Ehrlichia canis and Anaplasma platys. In the present study, the prevalence of tick-borne haemoparasites was assessed in dogs in  Agartala, Tripura. Blood samples were collected from a total of 1776 dogs irrespective of breed, age, sex and categories for a period of  one calendar year starting from March 2022 to February 2023. The overall prevalence of tick-borne haemoparasites in dogs was found  59.46 %(1056/1776) with only 11 cases of mixed infection. The study on the basis of breed, sex, age, season and category showed the  highest prevalence of tick-borne haemoparasites in German Spitz (77.20%), male dogs (63.57%), adult dogs (60.71%), monsoon season  (73.83%) and stray dogs (68.45%). The high prevalence of tick-borne haemoparasitic infection in dogs in the study area demands the  strategic control of tick population and effective management practices necessary to control tick-borne haemoparasitic infections.
Keywords: Agartala,; Dogs; Prevalence; Tick-borne haemoparasites; Tripura